Synthesis and study of photoelectrical properties of planar ensembles based on TiO2 and graphene oxide - А.Ж. Жумабеков; А.Е. Садыкова; Е.В. Селиверстова (Қарағанды университетінің хабаршысы. Физика сериясы)
In this paper, planar structures of various configurations based on TiO2 and graphene oxide are synthesized. Using SEM, it is shown that graphene oxide forms an insular film both on the surface and under the TiO2 layer during deposition. As well as SEM images show that TiO2 nanoparticles on the surface of graphene oxide are distributed as evenly as on the surface of FTO glass. The absorption spectra of synthesized films are a combination of the absorption curves of the original components. In this case, there is a shift of the absorption band of the planar structure nanocomposite to the longwave region. It is shown that in planar ensembles, the photoelectrochemical activity of films is higher only for the first lighting cycle. Research shows that the amount of graphene oxide affects not only the optical and photoelectrochemical properties, but also the electrical parameters. The latter, in turn, show that the resistance decreases by 1.3 times in the planar structure of graphene oxide with 30 layers. It was found that in planar structures of nanocomposite materials, the location of graphene oxide also affects the overall properties of the material. Research shows that the best indicators of photoinduced current generation are registered for the FTO/GO/TiO2 structure. Thus, a nanocomposite material in a planar structure based on TiO2 and graphene oxide depends on the architecture of the location and deposited volume of graphene oxide.